Development of Microfluidic Systems Enabling High-Throughput Single-Cell Protein Characterization - Fan, Beiyuan (Sensors (Basel), 2016)
This article reviews recent developments in microfluidic systems enabling high-throughput characterization of single-cell proteins. Four key perspectives of microfluidic platforms are included in this review: (1) microfluidic fluorescent flow cytometry; (2) droplet based microfluidic flow cytometry; (3) large-array micro wells (microengraving); and (4) large-array micro chambers (barcode microchips). We examine the advantages and limitations of each technique and discuss future research opportunities by focusing on three key performance parameters (absolute quantification, sensitivity, and throughput).